Novel Functional Mesoporous Silicas for Separating and Pre-Concentrating Trace Chromium Ion in Fireworks and Firecracker - Jiang, F.M.; Ren, F.L.; Liao, Q.L.; Fang, F.; Yi, T.F. (Asian Journal of Chemistry, 2014)
A sensitive and selective method has been developed for chromium ion in fireworks and firecracker, using functional mesoporous silica materials as the absorbents combined with the inductively coupled plasma optical emission spectrometer (ICP-OES) method. The mesoporous silica materials were functionalized with 2-mercaptobenzothiazole utilizing potassium iodide as catalyst and ecofriendly ethanol as solvent, which were applied in fabricating a minicolumn to preconcentrate the chromium solution, concentration of which was then determined by ICP-OES. The pre-concentration conditions including pH, temperature, adsorption time, eluent, elution time and effects of coexisting ions were discussed. The detection limit for Cr was 0.45 μg L-1 and the relative standard deviation for six replicate runs was 2.9 %. The proposed method has been applied to the determination of chromium ion in fireworks and firecracker samples with satisfactory results.